Metanálise de pesquisas brasileiras que tratam do desenvolvimento do pensamento algébrico na escola básica (1994-2014) - Pires, Flávio de Souza (Universidade Federal de São Carlos, 2017)
This study is a PhD thesis whose objective is to identify, describe and analyze what theoretical and methodological elements have been considered in Brazilian dissertations in Mathematics Education, from 1994 to 2014; which relationships with the development of algebraic thinking, their main contributions and challenges to the teaching of algebra in mathematics classes of basic education, more specifically mainstream education of primary school and secondary school. The issue that guides the research is defined as: which elements indications that composed algebraic thinking have been conceived and described by Brazilian studies in Mathematical Education from 1994 to 2014, and which of these elements have been prioritized in the teaching of algebra in basic education? For this, a qualitative meta-analysis was performed with 20 dissertations that composed the corpus analysis of the thesis, by taking into account as the theoretical basis for the data analysis the Ginzburg (1989) indiciary paradigm. We identified, starting from signs, a conception of ready and finished mathematics, the science of standards and regularities, which has an abstract thinking, a formal and symbolic language, by the researchers themselves. All these hypotheses can be identified in the memorials and interpretation of the theoretical references used in the research. Another evidence are the activities and didactic sequences elaborated by the teachers/researchers that prioritize in a certain section the formal algebra, symbolic, through the observation of regularities and numerical and/or geometric patterns in the process of teaching algebra. There is certainty that the use of activities involving regularities and patterns initiates algebraic thinking and little differentiation or deepening between the concepts of thought and language.
Keywords: Metanálise qualitativa; Desenvolvimento do pensamento algébrico; Paradigma do saber indiciário; Ensino de álgebra; Educação matemática; Qualitative meta-analysis; Development of algebraic thinking; Paradigm of indicial knowledge; Algebra teaching; Mathematical education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM